ANALISIS PENGENALAN PEMBELAJARAN CALISTUNG TAHAP DASAR DI KELAS I SDN TEMBONG 2 - Ria Mariana; Yessi Feronica Nuryati Silalahi; Hani Zakiyatun Nisa; Maya Alfina; Farhan Athif Oktavian; Chelsi Arnita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Reading,writing and arithmetic skills are important aspects in elementary school. Student need to master aspects of reading, writing and arithmetic. These three aspects have an important role in learning, because by reading, writing and arithmetic children can learn various ways to improve their knowledge. The introduction and cultivation of calistung abilities can begin when children enter the lower grade level which is at the age of 7-9 years, where at this stage student enter the concrete operational stage which has introductive end deductive reasoning. Therefore, the author conducted research on the analysis of the introduction to basic stage learning of reading, writing and arithmetic at SDN Tembong 2. The method used in this research was a qualitative approach with descriptive analysis method. Based on the result obtained from research, improving students reading, writing and arithmetic skills can be done by a playing several methods. In reading activities, researchers use the letter recognition method to provide an introduction for students who still have difficulty remembering the letters of the alphabet. Letter recognition is carried out using the singing method. This aims to ensure that students can remember each letter of the alphabet fluently. Regarding writing skills, almost all stardom still cannot write neatly and almost all student cannot differentiate between uppercase and lowercase letters. Regarding numeracy skills, there are some student who still cannot count but already known number. Based on this, in researcher introduced the finger method four students in order to provide an understanding of counting using the fingers.